ACC deaminase-producing endophytic fungal consortia promotes drought stress tolerance in M.oleifera by mitigating ethylene and H2O2 - Rehman, Bushra; Javed, Javeria; Rauf, Mamoona; Khan, Sumera Afzal; Arif, Muhammad; Hamayun, Muhammad; Gul, Humaira; Khilji, Sheza Ayaz; Sajid, Zahoor Ahmad; Kim, Won-Chan; Lee, In-Jung (Frontiers in Plant Science, 2022)
Introduction Drought has become more prevalent due to dramatic climate change worldwide. Consequently, the most compatible fungal communities collaborate to boost plant development and ecophysiological responses under environmental constraints. However, little is known about the specific interactions between non-host plants and endophytic fungal symbionts that produce growth-promoting and stress-alleviating hormones during water deficits. Methods The current research was rationalized and aimed at exploring the influence of the newly isolated, drought-resistant, ACC deaminase enzyme-producing endophytic fungi Trichoderma gamsii (TP), Fusarium proliferatum (TR), and its consortium (TP+TR) from a xerophytic plant Carthamus oxycantha L. on Moringa oleifera L. grown under water deficit induced by PEG-8000 (8% osmoticum solution). Results The current findings revealed that the co-inoculation promoted a significant enhancement in growth traits such as dry weight (217%), fresh weight (123%), root length (65%), shoot length (53%), carotenoids (87%), and chlorophyll content (76%) in comparison to control plants under water deficit. Total soluble sugars (0.56%), proteins (132%), lipids (43%), flavonoids (52%), phenols (34%), proline (55%), GA3 (86%), IAA (35%), AsA (170%), SA (87%), were also induced, while H2O2 (-45%), ABA (-60%) and ACC level (-77%) was decreased by co-inoculation of TP and TR in M. oleifera plants, compared with the non-inoculated plants under water deficit. The co-inoculum (TP+TR) also induced the antioxidant potential and enzyme activities POX (325%), CAT activity (166%), and AsA (21%), along with a lesser decrease (-2%) in water potential in M. oleifera plants with co-inoculation under water deficit compared with non-inoculated control. The molecular analysis for gene expression unraveled the reduced expression of ethylene biosynthesis and signaling-related genes up to an optimal level, with an induction of antioxidant enzymatic genes by endophytic co-inoculation in M. oleifera plants under water deficit, suggesting their role in drought stress tolerance as an essential regulatory function. Conclusion The finding may alert scientists to consider the impacts of optimal reduction of ethylene and induction of antioxidant potential on drought stress tolerance in M. oleifera. Hence, the present study supports the use of compatible endophytic fungi to build a bipartite mutualistic symbiosis in M. oleifera non-host plants to mitigate the negative impacts of water scarcity in arid regions throughout the world.